2018
DOI: 10.3389/fimmu.2018.01477
|View full text |Cite
|
Sign up to set email alerts
|

High Tidal Volume Induces Mitochondria Damage and Releases Mitochondrial DNA to Aggravate the Ventilator-Induced Lung Injury

Abstract: ObjectiveThis study aimed to determine whether high tidal volume (HTV) induce mitochondria damage and mitophagy, contributing to the release of mitochondrial DNA (mtDNA). Another aim of the present study was to investigate the role and mechanism of mtDNA in ventilator-induced lung injury (VILI) in rats.MethodsRats were tracheotomized and allowed to breathe spontaneously or mechanically ventilated for 4 h. After that, lung injury was assessed. Inhibition of toll-like receptor 9 (TLR9), named ODN2088, was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 51 publications
4
41
0
Order By: Relevance
“…Previous work in rats suggested that VILI damages mitochondria primarily through mitophagy, such that mitophagy-released mtDNA makes up a significant fraction of total mtDNA (Lin et al, 2018). Consistent with this idea, we found that A549 cells after CS at 20% tension up-regulated the level of mtDNA-79 and mtDNA-230 ( Figures 1G,H).…”
Section: Overstretching Of Lung Epithelial Cells Activates Mitophagy supporting
confidence: 90%
See 1 more Smart Citation
“…Previous work in rats suggested that VILI damages mitochondria primarily through mitophagy, such that mitophagy-released mtDNA makes up a significant fraction of total mtDNA (Lin et al, 2018). Consistent with this idea, we found that A549 cells after CS at 20% tension up-regulated the level of mtDNA-79 and mtDNA-230 ( Figures 1G,H).…”
Section: Overstretching Of Lung Epithelial Cells Activates Mitophagy supporting
confidence: 90%
“…It suggested that A549 cells before CS did not activate autophagy; A549 cells immediately after CS induced autophagy with autophagosomes; A549 cells at 4.0 h after the end of CS showed the advanced autophagy with autolysosomes. Our results suggested that our cell culture model of CS recapitulates the mitophagy-induced release of mtDNA that we observed in our rat model of mechanical ventilation (Lin et al, 2018).…”
Section: Overstretching Of Lung Epithelial Cells Activates Mitophagy supporting
confidence: 81%
“…However, mitochondrial ROS also participate in other cellular processes including the activation of mitochondrial permeability transition pore (mPTP), dysregulation of mitophagy, imbalances in mitochondrial dynamics, and programmed cell death [48]. These processes represent potential routes for mtDNA displacement following ROS burst as evidenced by the finding of oxidized mtDNA fragments outside of mitochondria in the setting of several metabolic diseases [43,[49][50][51][52][53] (Figure 1). Under several stressors (e.g., mitochondrial dysfunction and consequent reactive oxygen species (ROS) production, viral and bacterial infections), several types of damage are inflicted to mitochondrial DNA (mtDNA) and a set of signaling pathways are activated to promote mitochondrial recovery or demise depending on the damage severity.…”
Section: Failing Mitochondrial Quality Control and Mtdna Releasementioning
confidence: 99%
“…although essential in critically ill patients, mechanical ventilation often induces or aggravates lung injury, which is termed Vili (21). accumulating studies (22,23) have revealed that Vili is mainly characterized by increases in pulmonary vascular permeability, influxes of inflammatory cells and various cytokines. These inflammatory cells could produce inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%